THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND ANXIETY IN DIABETES MELLITUS AT RSUD DR. HARJONO PONOROGO IN 2023 - Wiratmoko, Heru; Purwaningsih, Endang; Suwanto, Agus Wiwit (Indonesian Journal of Health Science, 2024)
The prevalence of Diabetes Mellitus (DM) globally continues to increase until it triples in 2030, namely 21.3 million (Perkeni, 2019). Physical, psychological, economic and social changes occur due to various complications. Diabetes mellitus, which cannot be completely cured, often results in anxiety and decreases quality of life. The role of patients and families in managing DM is vital because DM is a chronic disease that patients will carry for life (Perkeni, 2019). The research aims to identify family support and the level of anxiety among patients with type 2 diabetes mellitus at the Internal Medicine Clinic, Dr. RSUD. Harjono Ponorogo. This research design used cross-sectional research with the Zung Self-Rating Anxiety Scale and Hensarling's Diabetes Family Support Scale). Data analysis used statistical tests with Spearman's Rink through the SPSS program with Î± of 5%. The results of the Spearman Rink test obtained a value (p-value = 0.027 Ë‚ 0.05) indicating that there is a significant relationship between family support and anxiety in patients with diabetes mellitus. Based on the results of the analysis, it is known that family support has a significant influence on the level of anxiety among patients with type 2 diabetes mellitus